Effects of Extraction Buffer on the Solubility and Immunoreactivity of the Pacific Oyster Allergens - Roni Nugraha; Thimo Ruethers; Elecia B. Johnston; Jennifer M. Rolland; Robyn E. O’Hehir; Sandip D. Kamath; Andreas L. Lopata (Foods, 2021)
Despite recent technological advances, novel allergenic protein discovery is limited by their low abundance, often due to specific physical characteristics restricting their recovery during the extraction process from various allergen sources. In this study, eight different extraction buffers were compared for their ability to recover proteins from Pacific oyster (Crassostrea gigas). The protein composition was investigated using high resolution mass spectrometry. The antibody IgE-reactivity of each extract was determined using a pool of serum from five shellfish-allergic patients. Most of the investigated buffers showed good capacity to extract proteins from the Pacific oyster. In general, a higher concentration of proteins was recovered using high salt buffers or high pH buffers, subsequently revealing more IgE-reactive bands on immunoblotting. In contrast, low pH buffers resulted in a poor protein recovery and reduced IgE-reactivity. Discovery of additional IgE-reactive proteins in high salt buffers or high pH buffers was associated with an increase in allergen abundance in the extracts. In conclusion, increasing the ionic strength and pH of the buffer improves the solubility of allergenic proteins during the extraction process for oyster tissue. This strategy could also be applied for other difficult-to-extract allergen sources, thereby yielding an improved allergen panel for increased diagnostic efficiency.